DNA nuclear targeting sequences for enhanced non-viral gene transfer: An in vitro and in vivo study - Yann T. Le Guen; Chantal Pichon; Philippe Guégan; Kévin Pluchon; Tanguy Haute; Sandrine Quemener; Juliette Ropars; Patrick Midoux; Tony Le Gall; Tristan Montier (Elsevier, 2021)
An important bottleneck for non-viral gene transfer commonly relates to translocation of nucleic acids into the nuclear compartment of target cells. So-called 3NFs are optimized short nucleotide sequences able to interact with the transcription factor nuclear factor κB (NF-κB), which can enhance the nuclear import of plasmid DNA (pDNA) carrying such motifs. In this work, we first designed a consistent set of six pDNAs featuring a common backbone and only varying in their 3NF sequences. These constructions were then transfected under various experimental settings. In vitro, cationic polymer-assisted pDNA delivery in five human-derived cell lines showed the potential advantage of 3NF carrying pDNA in diverse cellular contexts. In vivo, naked pDNAs were hydrodynamically delivered to muscle hindlimbs in healthy mice; this direct accurate comparative (in the absence of any gene carrier) revealed modest but consistent trends in favor of the pDNAs equipped with 3NF. In summary, the results reported emphasize the implications of various parameters on NF-κB-mediated pDNA nuclear import; under specific conditions, 3NF can provide modest to substantial advantages for pDNA gene transfer, in vitro as well as in vivo. This study thus further underscores the potential of optimized nuclear import for more efficient non-viral gene transfer applications.